Islamic Character Education as an Effort to Anticipate Intolerance and Disintegration - Nashiroh, Faiz; Az Zafi, Ashif (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2021)
This article aims to determine how to anticipate attitudes of intolerance and disintegration that occur in Indonesia. This article uses a descriptive research method. The data was collected by conducting a literature study with information from respondents. In the process, the writer uses a qualitative approach. The author found an effort to anticipate attitudes of intolerance and disintegration by planting Islamic character education with the habituation method in all spheres of life. The results obtained from this study are that intolerance and disintegration can be anticipated by planting Islamic character education with the method of habituation in all spheres of life, both family, school, and society.